Co-intercalated layered double hydroxides as thermal and photo-oxidation stabilizers for polypropylene - Zhang, Qian; Gu, Qiyu; Leroux, Fabrice; Tang, Pinggui; Li, Dianqing; Feng, Yongjun (Beilstein Journal of Nanotechnology, 2018)
An elegant and efficient approach consisting in the co-intercalation of stabilizing molecular anions is described here. The thermal stabilizer calcium diethyl bis[[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate] (Irganox 1425, MP-Ca) and a photo-oxidation stabilizer (hindered amine light stabilizer, HALS) are co-intercalated into the interlayer regions of layered double hydroxides (LDH) in a one-step coprecipitation. These hybrid organic–inorganic materials are successively dispersed in polypropylene to form HnMn′-Ca2Al/PP composite films (with H = HALS and M = MP) through a solvent casting method. The corresponding crystalline structure, chemical composition, morphology as well as the resistance against thermal aging and photo-oxidation are carefully investigated by various techniques. The results show that the powdered HnMn′-Ca2Al-LDHs hybrid materials have a much higher thermal stability than MP-Ca and HALS before intercalation. In addition, the HnMn′-Ca2Al/PP composites exhibit a higher overall resistance against thermal degradation and photo-oxidation compared to LDHs intercalated with only HALS or MP. This underlines the benefit of the co-intercalation. The co-intercalated LDH materials pave a new way in designing and fabricating high-performance multifunctional additives for polymers.
Keywords: co-intercalation; composites; layered double hydroxides; photo-oxidation stability; polypropylene; thermal stability